2011
DOI: 10.1097/ico.0b013e3182031ca0
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Melt of Incisions Overlying Corneal Ring Segments: Case Series and Literature Review

Abstract: : Corneal melt is a rare complication of ICRS. We conclude that wound gape over ICRS contributes to the development of melt. Strategies can be employed to reduce the incidence of this rare but important complications of ICRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Ultrastructural features of the PMD cornea such as breaks in Bowman's layer, disorganization of collagen fibrils (CFs) in the stroma, and degeneration of Descemet's membrane have been reported previously (Pouliquen et al, 1987). Corneal melt was also observed in the eyes suffering with PMD (Kugler et al, 2011). Hassell and Birk (2010) reported that the extracellular matrix of corneal stroma consists of collagen with lesser amount of proteoglycans (PGs).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Ultrastructural features of the PMD cornea such as breaks in Bowman's layer, disorganization of collagen fibrils (CFs) in the stroma, and degeneration of Descemet's membrane have been reported previously (Pouliquen et al, 1987). Corneal melt was also observed in the eyes suffering with PMD (Kugler et al, 2011). Hassell and Birk (2010) reported that the extracellular matrix of corneal stroma consists of collagen with lesser amount of proteoglycans (PGs).…”
Section: Introductionmentioning
confidence: 72%
“…Ultrastructural features of the PMD cornea such as breaks in Bowman's layer, disorganization of collagen fibrils (CFs) in the stroma, and degeneration of Descemet's membrane have been reported previously (Pouliquen et al, ). Corneal melt was also observed in the eyes suffering with PMD (Kugler et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…Melting is also a known complication of intracorneal stromal ring segments (ICRS) for ectasia or keratoconus . The author concluded that wound gape over ICRS contributes to the development of melting.…”
Section: Aetiologymentioning
confidence: 99%
“…Radial keratotomy weakens the cornea, and the potential complications of the surgery include loss of best-corrected vision acuity, infection, and rupture of the globe. [7][8][9] Radial keratotomy may also induce corneal instability and induce diurnal fluctuation of refractive error and hyperopic shift. 10 …”
Section: Refractive Surgerymentioning
confidence: 99%